2016
DOI: 10.3832/ifor1905-009
|View full text |Cite
|
Sign up to set email alerts
|

Linking nursery nutritional status and water availability post-planting under intense summer drought: the case of a South American Mediterranean tree species

Abstract: (1-2) Drought-avoidance traits of South American Mediterranean tree species are crucial attributes to be considered in nursery practices aimed at improving the performance of seedlings exposed to intense summer drought in dryland reforestation projects. In this study, we determined the relation between nursery fertilization doses and the development of drought-avoidance traits of the soapbark tree Quillaja saponaria (Mol.) under contrasting watering regimes following post-planting. Seedlings were grown for 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Under dry soil conditions, the large seedlings showed high levels of water stress. Other field or controlled experiments have substantiated this relationship between seedling size and water stress (Lamhamedi et al 1998, Ovalle et al 2016), but only a few of them have analyzed how the relationship between seedling size and soil moisture impacts ψMD (Stewart & Bernier 1995, Lamhamedi et al 1997). Furthermore, the controlled conditions experiment performed here shows that large seedlings are not more stressed during the first weeks after planting than small ones if soil moisture is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under dry soil conditions, the large seedlings showed high levels of water stress. Other field or controlled experiments have substantiated this relationship between seedling size and water stress (Lamhamedi et al 1998, Ovalle et al 2016), but only a few of them have analyzed how the relationship between seedling size and soil moisture impacts ψMD (Stewart & Bernier 1995, Lamhamedi et al 1997). Furthermore, the controlled conditions experiment performed here shows that large seedlings are not more stressed during the first weeks after planting than small ones if soil moisture is high.…”
Section: Discussionmentioning
confidence: 99%
“…However, in very dry areas, or during dry planting years when access to water is uncertain, the most appropriate seedling size for planting continues to be a matter of debate. Under these environmental conditions, planting small seedlings is considered to be a conservative strategy that can be expedient insofar as planting shock is reduced by minimizing shoot water losses (Lamhamedi et al 1997, Trubat et al 2010, Cortina et al 2013, Ovalle et al 2016. Notwithstanding this, the specific literature on dry areas is somewhat contradictory, with studies showing that seedling size has positive , Villar-Salvador et al 2012, 2013b, Oliet et al 2013, Tsakaldimi et al 2013 or negative effects (Trubat et al 2008, Zida et al 2008, Cortina et al 2013, Ivetic et al 2016 or both (Navarro et al 2006) on planting performance.…”
Section: Introductionmentioning
confidence: 99%
“…There is a well‐documented positive relationship between seedling quality and successful restoration for numerous tree species (Villar‐Salvador et al ; Oliet et al ; Ovalle et al ). For better seedling quality, native plant producers in Chile need a technological leap to improve and update their production protocols, infrastructure, and materials in their nurseries.…”
Section: Bottlenecks For Forest Restoration In Chilementioning
confidence: 99%
“…The intensity of drought, site conditions and species' response can explain these differences (Villar-Salvador et al 2012b). Ovalle et al (2016) found that high fertilized Q. saponaria seedlings established in Mediterranean field conditions (i.e., dry period of seven months) did not show a superior performance when contrasted to unfertilized ones. In extremely harsh Mediterranean environments, low fertilized seedlings are considered more resistant to drought because they reduce leaf area and increase root biomass (Hernández et al 2009), both characteristics of a drought tolerant genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Seedling quality and nursery culture regimes for Q. saponaria seedlings have received little attention in Chile (e.g., Ovalle et al 2016). Thus, in an effort to contribute to the understanding of Q. saponaria nursery culture, we initiated a preliminary study aimed at determining the influence of watering, container size and fertilization level on the early growth, survival and physiological responses of the species.…”
Section: Introductionmentioning
confidence: 99%